Awareness of Cancer-Related Malnutrition and Its Management: Analysis of the Results From a Survey Conducted Among Medical Oncologists - Muscaritoli, Maurizio; Corsaro, Emanuele; Molfino, Alessio (Frontiers in Oncology, 2021)
Cancer is a global major public health problem, particularly in Western countries, where it represents the second leading cause of death after cardiovascular disease. Malnutrition is common in cancer patients and differs from starvation-related malnutrition, as it results from a combination of anorexia and metabolic dysregulation, caused by the tumor itself or by its treatment, and causing cachexia. Cancer-associated malnutrition can lead to several negative consequences, including poor prognosis, reduced survival, increased therapy toxicity, reduced tolerance and compliance to treatments and diminished response to antineoplastic drugs. Guidelines issued by the Ministry of Health in 2017, the most recent ESPEN guidelines and the PreMiO study highlighted an inadequate nutritional support in cancer patients since their first visit, and recommended an optimization of the quality of life of cancer patients in each stage of the disease, also through specific nutritional interventions by multidisciplinary teams. Based on the evidences summarized above, a survey has been carried out on a sample of 300 Italian hospital medical oncologists to evaluate their level of awareness and perception of cancer-related malnutrition and their proposals to implement effective strategies to improve nutritional care in the setting of hospital oncology departments in Italy. The survey results indicate that, despite high levels of awareness among Italian oncologists, malnutrition in cancer patients remains, at least in part, an unmet medical need, and additional efforts are necessary in terms of increased training and hiring of personnel, and of creation of organizational pathways aimed at treatment optimization based on available evidences.